Development peculiarities of modern Belarus corporate editions - Zayats, Nikolai V. (Journal of the Belarusian State University. Journalism, 2019)
The study topic is based on the features of the functioning of corporate publications at the current stage of their development. By the means of the example of Belarusian banking publications, the study examines the problem of differentiation of corporate publications, suggests definitions for corporate publications, corporate media, corporate press, identifies innovations in the structure of corporate publications, and explores their target audiences.